Penggunaan Suhu Dan Dosis Propolis Yang Berbeda Terhadap Nisbah Kelamin Ikan Guppy (Poecilia Reticulata) - Mulyasih, Dwi; -, Tarsim; Sarida, Munti (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2012)
Guppy (Poecilia reticulata) is one of undifferentiated sex species that can direct to produce male during embryogenesis and larvae phase. Temperature is relevant environment factors that affect to gonad differentiation in fish. Propolis is a material from honeybees that has potential to be used in sex reversal to replaced 17α-metiltestosteron. Propolis contains chrysin and galangin with the function inhibited testosteron to estradiol conversion. The aim of this research is to determine the best treatment among different ambient temperature and propolis on different dose. The research was conducted in factorial randomize design, using twelve treatments. The treatments were given to pregnant guppy brood stock for 24 hours that were immersed in interaction of ambient temperature 28; 30 and 32oC with propolis on different dose 0; 25; 75 and 100 µl/l. The result showed that interaction between temperature and propolis showed significant difference in producing male guppy (P<0.05) with high percentage of males equal to  68.72 ± 1.91% in the treatments interaction between temperature 32oC and 25µl/l propolis dose, that has given different significantly with others. The treatments were not stimulate the intersex stocks (P>0.05).